Thermoplastic starch/natural rubber blends - Carvalho, AJF; Job, A. E.; Alves, Neri [UNESP]; Curvelo, AAS; Gandini, A. (Elsevier B.V., 2003)
Thermoplastic starch/natural rubber polymer blends were prepared using directly natural latex and cornstarch. The blends were prepared in an intensive batch mixer at 150 degreesC, with natural rubber content varying from 2.5 to 20%. The blends were characterised by mechanical analysis (stress-strain) and by scanning electron microscopy. The results revealed a reduction in the modulus and in tensile strength, becoming the blends less brittle than thermoplastic starch alone. Phase separation was observed in some compositions and was dependent on rubber and on plasticiser content (glycerol). Increasing plasticiser content made possible the addition of higher amounts of rubber. The addition of rubber was, however, limited by phase separation the appearance of which depended on the glycerol content. Scanning electron microscopy showed a good dispersion of the natural rubber in the continuos phase of thermoplastic starch matrix. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: starch; natural rubber; biodegradable blends